Frequency of Gastrointestinal Parasites and Egg per Gram Faeces Count of Nematodes in Black Bengal Goat under Field Condition in West Bengal, India - Dhara, K. C; Ray, N; Lodh, C; Bandopadhyay, P.K; Goswami, A (International Journal of Veterinary Sciences Research, 2015)
Prevalence as well as intensity of infection of gastro-intestinal parasites in Black Bengal goat under field condition in different season was done to assess the prevalence of gastro-intestinal parasites in Black Bengal goat under field condition to guide farm managers. The Coprological study of faecal samples of apparently healthy Black Bengal goat was conducted in field condition at Nadia district of West Bengal state of India from July 2005 to June 2006 through direct microscopic examination as well as floatation and sedimentation methods. Out of 1147 faecal samples examined, 715 (62.34%) samples were found to be positive for gastrointestinal parasites. Strongyle sp. was the most prevalent (77.48%) parasites followed by Paramphistome sp. (30.63%), Trichuris (14.55%), Moneizia (12.73%) and Fasciola sp. (6.29%). Seasonal prevalence rate and eggs per gram of faeces (EPG) count was highest in monsoon and lowest in summer. Monthly EPG count and prevalence rate was highest in November followed by October and September.The present study might help to decide the deworming schedule and management measures for farmers to increase the productivity of Black Bengal.